PROJETO EDUCA SERE III - A CARTA IMAGEM DE SÃO JOSÉ DOS CAMPOS - Sausen, Tania Maria; Ruddorff, Bernardo T.; Ávila, João; Simi Filho, Romeu; Almeida, Wellington Rodolfo Castilho de; Rosa, Viviane Gomes C. da; Godoi Filho, Joaquim (Boletim de Geografia, 2011)
<>